2012
DOI: 10.5829/idosi.ijee.2012.03.05.11
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Electricity Consumption in Crushing and Grinding Processes of Traditional and Urban Gold Mining by Using Life Cycle Assessment (LCA)

Abstract: Abstract:Mining is not only an essential component of social and economic development since prehistoric time, but it also gives a large impact on our civilization. Gold is a noble metal that is highly valued. The extraction of minerals from earth is known as traditional mining. Gold also can be extracted from electronic waste or e-waste, and this new concept is called urban mining. There are many stages in traditional and urban mining process. However, in this study, the focus was on crushing and grinding proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…gold), because of different mining methods, the results of the current analysis are inconsistent with some previous studies. In a sense, [7], [29], [30] reported that the utilization of electricity for mineral processing and mining operation was the largest contributor to total carbon emissions. Of this total, more than 50 to 80 percent of total electricity was used for crushing and grinding processes of gold mining [29]- [31].…”
Section: Embodied Energymentioning
confidence: 99%
“…gold), because of different mining methods, the results of the current analysis are inconsistent with some previous studies. In a sense, [7], [29], [30] reported that the utilization of electricity for mineral processing and mining operation was the largest contributor to total carbon emissions. Of this total, more than 50 to 80 percent of total electricity was used for crushing and grinding processes of gold mining [29]- [31].…”
Section: Embodied Energymentioning
confidence: 99%
“…This result is consistent with previous studies [22]- [24] that the combustion of fossil fuels to generate electricity is the largest source of CO2 emissions. Of these, more than 50 % of total electricity was used for crushing and grinding processes [25]. In comparison with other mines, [18] found that GHG emissions from lignite and limestone mining in Thailand were approximately 571,539 and 20,878 tCO2e per annual production capacity, respectively.…”
Section: Quantification Of Ghgs Emissionmentioning
confidence: 99%
“…Among these, the life cycle assessment (LCA) methodology [31] is used to assess the environmental benefits obtained choosing innovative materials containing slag instead of similar conventional products. The majority of these LCA analyses are related to the use of different types of industrial by-products [32][33][34][35][36][37] with the exception of other authors who have evaluated the environmental burden of copper slag [38][39][40][41][42][43][44]. As Kua [42,43], who has investigated copper slag recycling for cement and natural sand replacement and, De Schepper et al [44] who has assessed the environmental burdens of a concrete using different secondary products among these the CS as substitute of natural sand.…”
Section: Introductionmentioning
confidence: 99%